Spin-glass magnetic ordering in CoMgGaO₂BO₃ ludwigite - Ivanova, N.B.; Platunov, M.S.; Knyazev, Yu.V.; Kazak, N.V.; Bezmaternykh, L.N.; Eremin, E.V.; Vasiliev, A.D. (Физика низких температур, 2012)
The single crystal needle shape samples of diamagnetically diluted cobalt ludwigite CoMgGaO₂BO₃ have
been grown by the flux method. The results of x-ray diffraction and both dc and ac magnetic measurements are
presented. The unit cell volume undergoes a noticable growth under dilution from 328.31 Å3
for the parent compound
Co₃O₂BO₃ to 345.46 Å³
for CoMgGaO₂BO₃. The temperature of magnetic transition is considerably
lower for the latter compound (25 K against 43 K for Co₃O₂BO₃). The dc magnetization temperature dependencies
undergo the splitting of field cooled and zero-field cooled regimes and the ac magnetic susceptibility
temperature dependencies are frequency dependent pointing out a possible spin-glass freezing in the magnetic
system.